Downregulated FOXO3a Associates With Poor Prognosis and Promotes Cell Invasion and Migration via WNT/β-catenin Signaling in Cervical Carcinoma - Tian, Yuejun; Qi, Ping; Hu, Xuemei (Frontiers in Oncology, 2020)
Background: Emerging studies have demonstrated that the Forkhead transcription factor FOXO3a is closely correlated with the progression of multiple tumors. Nevertheless, the biological role and prognostic value of FOXO3a have yet to be fully elucidated in cervical carcinoma. This study was designed to determine the molecular mechanism and prognosis of FOXO3a in cervical carcinoma. Methods: The protein levels of FOXO3a were detected using immunohistochemistry and Western blotting. The relationships between FOXO3a expression and clinicopathological variables were analyzed. The biological mechanism of FOXO3a in cervical carcinoma cells (HeLa and CaSki) was investigated. We also explored the effect of FOXO3a on WNT/β-catenin signaling with respect to its expression and function. Results: The results demonstrated that decreased FOXO3a expression was related to increased tumor stage and grade, positive lymph node metastasis, and poor survival outcome in cervical carcinoma. Survival analysis revealed that the FOXO3a level is an independent prognostic factor for cervical carcinoma patients. Furthermore, the data indicated that the downregulation of FOXO3a expression promotes cell invasion and migration, while FOXO3a overexpression exhibited the opposite effects on cervical carcinoma. In addition, FOXO3a acted as a negative regulator of the canonical WNT/ β-catenin pathway in cervical carcinoma. Moreover, overexpression of FOXO3a also inhibited the expression of MMP2 and MMP9. Conclusion: These results reveal that FOXO3a, serving as a tumor suppressor gene, could suppress cell invasion and migration via the WNT/β-catenin signaling pathway and indicates a good prognosis in cervical carcinoma.